2016
DOI: 10.1097/iop.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Ameloblastoma with Orbital Involvement: An Institutional Experience and Literature Review

Abstract: Purpose To describe 8 patients with orbital involvement by ameloblastoma and to review the literature on this topic. Methods The electronic medical records and pathology databases of the Hospital of the University of Pennsylvania were searched to identify all patients with histopathologically confirmed ameloblastoma diagnosed between 1990 and 2015. PubMed database was searched for all well-documented cases of maxillary ameloblastoma and ameloblastic carcinoma exameloblastoma with orbital involvement publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
(48 reference statements)
1
20
0
1
Order By: Relevance
“…This is similar to the average age of occurrence of ameloblastomas and implies that recurrences occur within a few years of treatment. Arotiba et al [17] and Milman et al [12] reported highest recurrence in the third and fourth decade. Recurrent cases showed male predilection with male female ratio similar to that of ameloblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the average age of occurrence of ameloblastomas and implies that recurrences occur within a few years of treatment. Arotiba et al [17] and Milman et al [12] reported highest recurrence in the third and fourth decade. Recurrent cases showed male predilection with male female ratio similar to that of ameloblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1206 cases of ameloblastoma were identified in 10 publications. Summary of studies included in the review regarding ameloblastoma in general and the recurrence rate is shown in Table I [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Section 1: Clinicopathological Features Of Ameloblastoma And...mentioning
confidence: 99%
“…Although ODOVTOS-International Journal of Dental Sciences radical surgery, including segmental or marginal resection of the jaw, is generally recommended, some authors have advocated more conservative methods as the first line treatment modality in some cases (3,12,23). Initial surgical approach correlated with risk of recurrence, local disease aggressiveness, and mortality (30), and enucleation exhibited most high recurrence rate in our study. Any recurrence will increase the degree of tissue damage and the need for further surgery.…”
Section: Discussionmentioning
confidence: 52%
“…Ameloblastomas are low-grade neoplasms of odontogenic epithelium that account for about 1% of all oral tumours and about 10% of odontogenic tumours [1]. They commonly occur in the mandible and involvement of the maxilla is reported to be about 20% [2,3]. Although they are considered to be benign tumours with a slow growth rate, they are locally aggressive with a high tendency for local recurrence if not removed completely [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although they are considered to be benign tumours with a slow growth rate, they are locally aggressive with a high tendency for local recurrence if not removed completely [1,4]. Rarely, these tumours have the potential of distance metastasis [3], whereby this phenomenon is associated with a prolonged tumour duration and multiple recurrences following surgical interventions [2]. When histologically benign-appearing ameloblastoma does metastasize, it is referred to as metastatic ameloblastoma [5].…”
Section: Introductionmentioning
confidence: 99%